2005
DOI: 10.3402/ijch.v64i4.18011
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of First Nations communities and drinking and driving

Abstract: Living in First Nations communities is socially complex, highly emotionally charged, and peer-pressured. Drinking and driving and alcohol abuse amongst First Nations people reflect the community social structure, daily pressures and norms of behavior. Hence, to reduce drinking and driving casualties amongst First Nations young people, intervention strategies must address systemic issues, namely local people's social realities, norms, as well as local and peer relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The second lesson to be learned is that there remains an oversimplified conception that most cases of end-stage liver disease in FN patients are the consequence of heavy alcohol consumption. While alcohol abuse constitutes a health problem in general and among some FN communities (17), it is noteworthy that many patients referred with presumed alcoholic cirrhosis actually have an autoimmune liver disorder when appropriately evaluated. Because multiple studies across Canada have documented a high prevalence of autoimmune liver disease in FN populations (5,6,10,18), all clinicians should be aware of this susceptibility to ensure adequate screening and correct diagnosis.…”
mentioning
confidence: 99%
“…The second lesson to be learned is that there remains an oversimplified conception that most cases of end-stage liver disease in FN patients are the consequence of heavy alcohol consumption. While alcohol abuse constitutes a health problem in general and among some FN communities (17), it is noteworthy that many patients referred with presumed alcoholic cirrhosis actually have an autoimmune liver disorder when appropriately evaluated. Because multiple studies across Canada have documented a high prevalence of autoimmune liver disease in FN populations (5,6,10,18), all clinicians should be aware of this susceptibility to ensure adequate screening and correct diagnosis.…”
mentioning
confidence: 99%
“…Other related research by Rothe 50 highlighted the fact that living in Aboriginal and First Nations communities is socially complex, highly emotionally charged, and peer pressured. Furthermore, this study shows that drinking and driving and alcohol abuse among Aboriginal and First Nations people reflect the community social structure, daily pressures, and norms of behavior.…”
Section: Resultsmentioning
confidence: 99%
“…This burden is exemplified by the fact that Alcohol was a factor in 6.4% of injuries incurred by First Nations youth and over one-quarter (27.1%) of assaults against First Nations youth (First Nations Centre, 2005). Rothe (2005) reported that within nine First Nations communities, respondents considered alcohol abuse and drinking and driving to be "normal, community-endorsed behaviours". The proportion of Status Indian deaths that are alcohol-related is nearly one-quarter (23.5%) while drug-induced deaths account for 6.2% of Status Indian deaths (First Nations Centre, 2005).…”
Section: Alcohol Addictionmentioning
confidence: 99%
“…High rates of alcohol-related morbidity and mortality have also been reported in Australia (Saggers & Gray, 1998). Reasons given by Indigenous individuals for their alcohol use include boredom associated with living in a communities of limited recreational and employment opportunities and need to self-medicate to anesthetize the pain of poverty, racism and violence; thus, it is more likely community social and economic structure rather than individual or cultural values that contribute to the high prevalence of alcohol abuse in Indigenous communities (Rothe, 2005).…”
Section: Alcohol Addictionmentioning
confidence: 99%